Shrimp farming and industry : sustainability, trade, and livelihoods - Rahman, A. Atiq.; Bangladesh Centre for Advanced Studies (Dhaka : Bangladesh Centre for Advanced Studies : University Press Ltd., 2006)
With reference to Bangladesh.
Includes bibliographical references and index.
Keywords: Shrimp culture -- Bangladesh